PENEGAKAN HUKUM TINDAK PIDANA NARKOTIKAN DI INDONESIA DENGAN PENDEKATAN ASPEK FILOSOFIS, SOSIOLOGIS, DAN AGAMA - Muhamad Sadi Is; Eddy Daulatta Sembiring (SOL JUSTICIA, 2021)
Law enforcement against narcotics crimes continues to be improved considering the number of cases from year to year is increasing. What is a factor in the increasing number of cases of drug crimes that are getting faster is also triggered by the development of information technology, where communication between users, dealers, and suppliers can easily take place via the internet. Therefore, to prevent and eradicate narcotics crimes in Indonesia in general, it can be done with three approaches, namely a philosophical approach, a sociological approach, and a religious approach.